2020
DOI: 10.3390/toxins12020062
|View full text |Cite
|
Sign up to set email alerts
|

P-Cresylsulfate, the Protein-Bound Uremic Toxin, Increased Endothelial Permeability Partly Mediated by Src-Induced Phosphorylation of VE-Cadherin

Abstract: The goal of our study was to investigate the impact of p-cresylsulfate (PCS) on the barrier integrity in human umbilical vein endothelial cell (HUVEC) monolayers and the renal artery of chronic kidney disease (CKD) patients. We measured changes in the transendothelial electrical resistance (TEER) of HUVEC monolayers treated with PCS (0.1–0.2 mM) similar to serum levels of CKD patients. A PCS dose (0.2 mM) significantly decreased TEER over a 48-h period. Both PCS doses (0.1 and 0.2 mM) significantly decreased T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…PCS also exhibits a role in endothelial activation, through increased expression of ICAM-1, MCP-1 and TF, which promotes adhesion of leukocytes to the endothelium. It inhibits proliferation, viability, and repair capabilities impairing nitric oxide (NO) signaling or increasing its permeability [ 167 ]. TMAO, a gut metabolite derived from the fermentation of dietary choline/phosphatidylcholine, L-carnitine or betaine, also induces endothelial damage, with activation of NALP3 inflammasome [ 168 ], cellular inflammation, ROS production, and has been associated with atherothrombosis [ 169 ].…”
Section: Gut Dysbiosis In Ckd and Uremic Toxins: Role In Inflammatmentioning
confidence: 99%
“…PCS also exhibits a role in endothelial activation, through increased expression of ICAM-1, MCP-1 and TF, which promotes adhesion of leukocytes to the endothelium. It inhibits proliferation, viability, and repair capabilities impairing nitric oxide (NO) signaling or increasing its permeability [ 167 ]. TMAO, a gut metabolite derived from the fermentation of dietary choline/phosphatidylcholine, L-carnitine or betaine, also induces endothelial damage, with activation of NALP3 inflammasome [ 168 ], cellular inflammation, ROS production, and has been associated with atherothrombosis [ 169 ].…”
Section: Gut Dysbiosis In Ckd and Uremic Toxins: Role In Inflammatmentioning
confidence: 99%
“…Uremic toxins contribute to structural damage of the endothelial monolayer, which results in increased permeability. In CKD patients, studies have detected disruptions to the structure of the endothelial monolayer in renal arteries [ 13 , 75 ]. Loss of endothelial integrity and enhanced permeability are also seen in the aortic endothelium of nephrectomized rats, an animal model of CKD [ 76 , 77 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 99%
“…Loss of endothelial integrity and enhanced permeability are also seen in the aortic endothelium of nephrectomized rats, an animal model of CKD [ 76 , 77 ]. In vitro, PCS, IS, and uremic serum reduced the transendothelial electrical resistance (TEER), which indicates an increase in endothelial permeability [ 75 , 78 , 79 ]. In this regard, studies have also found that uremic toxins induced F-actin cytoskeletal remodeling in endothelial cells, leading to changes in cell morphology [ 13 , 79 , 80 ].…”
Section: Endothelial Dysfunction In Ckdmentioning
confidence: 99%
See 2 more Smart Citations